Rethinking The Proteus Effect – Can our digital personas influence our offline selves? - Poleac, Gabriela (Technium Social Sciences Journal, 2023)
This paper seeks to clarify the notable phenomena known as the Proteus effect. This phenomena clarifies the ability of avatar characteristics within digital gaming environments to have a noticeable impact on people’s actions in the real world. The research question that informs the conceptual framework put forward in this academic discourse is the following: if the Proteus effect is clearly perceptible among members of online gaming communities, might it not possibly also apply to users of social networking platforms? The study will use an example from the science fiction anthology series “Black Mirror” to explain and support this theoretical claim. It is hypothesised that once people create a social media presence, they start creating a digital identity or “avatar”, the development of which has the potential to have a substantial impact on their behaviour in real life. The Proteus effect’s plausible expansion outside of the online gaming industry, where it was first documented, is the main hypothesis that this paper seeks to clarify through the use of a hypothetical scenario taken from modern cinematic narratives. This article’s hypothesis imagines a future in which people eventually become like their digital avatars, leading to a time when real people resemble their virtual counterparts.